2011
DOI: 10.1371/journal.pone.0023791
|View full text |Cite
|
Sign up to set email alerts
|

H5N1 Whole-Virus Vaccine Induces Neutralizing Antibodies in Humans Which Are Protective in a Mouse Passive Transfer Model

Abstract: BackgroundVero cell culture-derived whole-virus H5N1 vaccines have been extensively tested in clinical trials and consistently demonstrated to be safe and immunogenic; however, clinical efficacy is difficult to evaluate in the absence of wide-spread human disease. A lethal mouse model has been utilized which allows investigation of the protective efficacy of active vaccination or passive transfer of vaccine induced sera following lethal H5N1 challenge.MethodsWe used passive transfer of immune sera to investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 43 publications
(48 reference statements)
3
11
0
Order By: Relevance
“…2). A previous study demonstrated that a minimum neutralizing antibody concentration with a 1:16 endpoint titer is sufficient to provide complete protection against H5N1 viruses (38). Although antibody-mediated protection is suggested to be the main contributor of protection in our vaccine, T cells may also play a role.…”
Section: Discussionmentioning
confidence: 92%
“…2). A previous study demonstrated that a minimum neutralizing antibody concentration with a 1:16 endpoint titer is sufficient to provide complete protection against H5N1 viruses (38). Although antibody-mediated protection is suggested to be the main contributor of protection in our vaccine, T cells may also play a role.…”
Section: Discussionmentioning
confidence: 92%
“…For the MN assay, no standardized assay and no internationally accepted cutoff for seroprotection exists. The seroprotection MN titer cutoff of 1:20 is based on the previously demonstrated statistically significant correlation with the SRH area of 25 mm 2 (5) and validation in passive transfer challenge studies in mice (24). Licensure of the whole-virus H5N1 vaccine was granted by the European regulatory authorities based on data obtained using these validated MN and SRH assays (25,26).…”
Section: Methodsmentioning
confidence: 99%
“…NT antibodies in serum samples are usually assessed by means of the microneutralization (MN), either CPE (cytopathic effect)‐based or ELISA‐based, or the plaque‐reduction neutralization (PRNT) assay. In the present review, we focused on the CPE‐based MN assay, since this is the preferred method because of its simplicity of execution, its ability to evaluate large numbers of samples, and the standardization of the quantity of virus used in the assay . Along with the ELISA sIgA assay, the MN assay constitutes a valid approach to evaluate the immunogenicity of LAIVs, IIVs, or recombinant influenza vaccines (eg rHA) in inducing selective anti‐influenza antibodies with influenza virus–neutralizing potential.…”
Section: Neutralizing (Nt) Antibodies In Nasal Wash/swab and Future Amentioning
confidence: 99%